العمل التطوعي والعمل الخيري في المنظور القرآني: Volunteerism and Philanthropy in the Quranic Perspective - Abed Abbas, Widad; Mohd Amat, Robiatul Adawiyah; Islam, Tajul (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
It is widely known that there is no synonym between the words of the Holy Quran. Each word has its own independent meaning, but it may be related with another word in raising new meaning or a specific meaning that Allah Almighty decreed. Sometimes confusion occurred between the terms because of apparently convergence and each term indicates specific point for the consequent legitimacy. This is the case with the terms of al-‘amal al-tatawwu’i (volunteerism) and al-‘amal al-khayri (philanthropy) frequently used throughout the text in many of the Muslim writings. Hence this research aims to explore the concept of “philanthropy” and “volunteerism” as mentioned in the Holy Quran as well as to elucidate the area of consensus and dissension between the two terms. One of the most important findings of this study through the inductive and analytical approach is that “volunteerism” is more general and extensive compared to “philanthropy”. The term “volunteerism” refers to the work or action regardless of the good or bad of an approach. Yet from Islamic perspective, the concept of “philanthropy” is accepted if only conforming to the higher objectives of Shari’ah in contradistinction to those who adopted this term as general or similar meaning to “volunteerism” in their writings.